The Implementation of Problem Solving-Based Scientific Learning to Improve Motivation and Learning Outcomes of Class IV Elementary School Students (Journal of Primary Education, 2020)
The research was conducted to apply an effective model of learning in improving motivation and learning outcomes of students by using problem solving-based scientific learning. The study is an experimental research with quasi design. The samples were taken from SD Kluwut 02 and SD Grinting 01. One class was taught using problem solving-based scientific learning model and the other class thaught using convensional model. The results of this research show that there was a significant increase in motivation and learning outcomes. It was obtained an increase the average learning motivation score by 4.86% and learning outcomes by 39.4%. Learning motivation had a positive and significant effect on learning outcomes with an influence of 24.55%. Students responded very well to learning theme 8 and sub theme 3 using problem solving- based scientific learning model. It concluded that this learning model is is very effective and recommended to be applied in elementary schools.